Development of ethics and welfare in the animal husbandry: 1st Part – The human-animal relationship in Judaism and Christianity - Sipos, Mihály; Móró, Adrienn; Szűcs, Endre (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
The aim of the article is to discuss and make a review of a topic often disputed nowadays, which is the issue of ethics and welfare in the animal husbandry. This study on the one hand gives a detailed introduction to the concepts of Judaism and Christianity concerning the relationship between humans and animals, on the other hand reviews the modern philosophical concepts.